Positioning Usa in the Chinese Outbound Travel Market - Li, Xiang (Robert); Cheng, Chia-Kuen; Kim, Hyounggon; Li, Xiangping (Journal of hospitality & tourism research (Washington, D.C.), 2015)
This study attempts to understand the position of the United States against its major non-Asian competitors in Mainland Chinese tourists’ minds. A multistep procedure of destination positioning analysis was designed, which involved a combination of multidimensional scaling, correspondence analysis, and logistic regression analysis. Furthermore, this study connects positioning analysis with market segmentation research, as the perceptual mapping analyses were performed at both aggregate and segment levels. Overall, it was found that the United States holds a unique position that is isolated from all other five destinations. The authors discussed the theoretical and managerial implications of the findings.